The moderating role of father involvement in the association between maternal depression and child nutrition: A cross-sectional study in rural Malawi - Suhyoon Choi; Yaeeun Han (PLoS ONE, 2025)
This study highlights the critical role of fathers in improving child dietary diversity in low-resource setting, particularly in the context of maternal mental health challenges. Using cross-sectional data of 333 mother-father-child triads in rural Malawi, we examine the association between paternal involvement and child dietary diversity among children aged between 24–60 months. Our findings show that greater father involvement is significantly associated with higher child dietary diversity scores, even after accounting for maternal depressive symptoms. Importantly, we identify a significant interaction between father involvement and maternal depressive symptoms: paternal engagement buffer the negative effects of maternal mental health challenges on children’s diets. However, father involvement does not correlate with household-level dietary diversity, suggesting that paternal contributions are targeted specifically toward children- primarily through the reallocation of nutrient-rich, animal-sourced foods. These results underscore the importance of culturally sensitive, family-centered nutrition interventions that actively engage fathers while addressing maternal mental health to improve child nutrition outcomes in low-resource contexts.